Bolivia: Impact of Shocks and Poverty Policy on Household Welfare - Gover Barja Daza; Javier Monterrey Arce; Sergio Villarroel Böhrt (Revista Latinoamericana de Desarrollo Económico, 2006)
This paper evaluates the short term impacts on poverty of pro-poor expenditure and total social expenditure during the 1998-2002 period of Bolivian economic recession. Observed characteristics of recession are simulated by the combined effects of negative terms of trade shock, reduction in foreign saving flows and low output growth. Evaluation is performed by simulating the impacts of shocks and social expenditures in an environment of low growth: i) on macro aggregates of consumption, income, saving and prices (based on a simple static 1-2-3 model), ii) on household income and consumption levels, and iii) on consumption based poverty indicators. The following were main results from experiments:The terms of trade shock had greater negative impact on household income then reduction in foreign saving flows. In contrast, reduction in foreign saving flows had greater negative impact on household consumption then the terms of trade shock. The head count ratio has been greater from reduction in foreign saving flows then from the terms of trade shock. Poverty gap and poverty intensity has concentrated in rural areas, being greater from reduction in foreign saving flows then from the terms of trade shock.The combined positive effects from observed social expenditure policy and effort in an environment of low output growth, did not compensate the combined negative impacts from the experienced terms of trade shock and reduction in foreign saving flows.These conclusions show that under macroeconomic disequilibrium poverty reduction efforts become policies of poverty containment or safety net programs. Poverty reduction is a long term objective that requires long term commitment for an environment on macroeconomic stability.
Additional information: The Governments of the United Kingdom and the Netherlands, the International Monetary Fund, and the World Bank have launched an international research project on the macroeconomic challenges faced by low income countries. The main goal of the project (coordinated by the Global Development Network) was to obtain the perspectives and insights of academics based in low income countries on the effectiveness and scope for improvement of macroeconomic policies in their economies. The paper was formally presented as the opening paper in the project's conference, IMF Headquarters, Washington DC, February 15-16, 2005. The authors would like to acknowledge comments from Raimundo Soto to this paper and its earlier version. Errors are our own. The authors gratefully acknowledge the financial support from GDN as well as its administrative support through Gary McMahon.
Keywords: 330; Terms of trade shock; Social expenditure; Household welfare; Poverty gap and intensity